2015
DOI: 10.1371/journal.pone.0115831
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Modified Citrus Pectin Induces Apoptosis-Like Cell Death and Autophagy in HepG2 and A549 Cancer Cells

Abstract: Cancer is still one of the leading causes of death worldwide, and finding new treatments remains a major challenge. Previous studies showed that modified forms of pectin, a complex polysaccharide present in the primary plant cell wall, possess anticancer properties. Nevertheless, the mechanism of action of modified pectin and the pathways involved are unclear. Here, we show that citrus pectin modified by heat treatment induced cell death in HepG2 and A549 cells. The induced cell death differs from classical ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 39 publications
3
32
0
1
Order By: Relevance
“…Among many biodegradable natural polysaccharides, pectin, primarily composed of poly-d-galacturonic acid bonded via α-1,4-glycosidic linkage, is being largely investigated as a colloidal stabilizer, gelling, thickening, and preventive/therapeutic agent [14,45]. Pectin molecules can act as a source for the suppression of cancer progression [46][47][48]. Furthermore, this molecule offers several advantages due to active molecules, which include easy complexation and self-assembly of small or larger molecules [14].…”
Section: Discussionmentioning
confidence: 99%
“…Among many biodegradable natural polysaccharides, pectin, primarily composed of poly-d-galacturonic acid bonded via α-1,4-glycosidic linkage, is being largely investigated as a colloidal stabilizer, gelling, thickening, and preventive/therapeutic agent [14,45]. Pectin molecules can act as a source for the suppression of cancer progression [46][47][48]. Furthermore, this molecule offers several advantages due to active molecules, which include easy complexation and self-assembly of small or larger molecules [14].…”
Section: Discussionmentioning
confidence: 99%
“…Other strategies for activating autophagy in tumor cells are based on more general attempts to suppress cancer cells or stimulate cancer cell death [ 36 , 37 ]. Several studies have shown that cancer cells exposed to autophagy inducers exhibit upregulation of autophagic activity resulting in suppression of tumor progression in human lung cancer, colorectal cancer, and breast cancer cells [ 39 , 40 , 41 , 42 ]. With respect to maintenance of bone homeostasis, Sambandam et al [ 27 ] demonstrated that autophagy induced by simulated microgravity modulates osteoclastogenesis and may regulate bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has been implicated in multiple diseases including neurodegenerative diseases, cardiovascular diseases, ischemia, traumatic brain injury, pulmonary diseases and cancer [61, 67, 68]. Mitophagy has been related to AD, Parkinson's disease (PD) and Huntington disease (HD) [69].…”
Section: Mitochondrial Fission Fusion and Autophagy (Mitophagy)mentioning
confidence: 99%